Competencies of Project Managers in Contemporary Organizations: A Survey Study of Project Managers in Poland - Wieslaw LUKASINSKI and Piotr ROMANSKI (Communications of International Proceedings, 2024)
This paper presents the competencies of project managers in contemporary organizations, focusing particularly on those leading projects in Poland. The motivation for this study arises from the growing importance of managerial competencies in light of dynamic changes within organizations and increasing demands on project leaders. Modern organizations face challenges in managing teams, especially with globalization, technological advancements, and shifting market needs. Despite extensive research on managerial competencies, there is still insufficient knowledge about which project manager competencies most influence project success in a complex and evolving environment. This study aims to address this gap by identifying key competencies crucial to project managers, especially in the context of the Polish market and the specific challenges faced by leaders in Poland. The research was conducted using a survey method targeting project managers across various industries, with a focus on their impact on project performance. Findings reveal that interpersonal competencies, such as communication, decision-making, and team motivation, are as important as technical skills, such as risk and budget management. The study also confirms that an effective project manager must combine leadership and analytical abilities, as well as manage teams, time, and relationships with stakeholders effectively. The study’s conclusions emphasize that organizations should invest in developing their project managers' soft skills, including communication, team motivation, and time management.
Keywords: : project manager competencies; project management; interpersonal competencies; project effectiveness